EFEKTIFITAS PELAKSANAAN PEMBERDAYAAN PEGAWAI NEGERI SIPIL PADA RUMAH SAKIT BHAYANGKARA PONTIANAK - Syarifah Irma Maulina E.01107126 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
This thesis writing is intended to provide input to the leadership and staff at the Hospital of Bhayangkara Pontianak about how empowerment of the employee on the research sites in improving health services in the work environment. In the Hospital of Bhayangkara there is some indication of the problem that must be more repaired again through concepts of empowerment that is increased of competence, giving authority and responsibility, giving confidence, giving motivation, and appropriate staffing. This had intended to be created efficient employee. Keywords : Effectiveness of Service, Employee Empowerment, and Health Services.